The influence of professional identity, job satisfaction, burnout on turnover intention among village public health service providers in China in the context of COVID-19: A cross-sectional study - Zhang, Xuewen; Zhang, Wenjie; Xue, Li; Xu, Zongyou; Tian, Zhuang; Wei, Chao; Zhang, Ying; Dong, Zhihuan; Gao, Shansong (Frontiers in Public Health, 2022)
Background In China, COVID-19 has undoubtedly posed a huge challenge to the capacity of rural public health services. Village public health service providers are responsible for reporting and dealing with infectious diseases and public health emergencies. However, the turnover of village public health service providers is gravely threatening the stability of rural primary health system step by step. This study systematically evaluated the effects of professional identity, job satisfaction, burnout on turnover intention of village public health service providers, and further measured the mediating effect of job satisfaction and burnout between professional identity and turnover intention. Methods From May to June 2019, 1,244 village public health service providers in Shandong Province were selected as the research objects. Sociodemographic characteristics, professional identity, job satisfaction, burnout and turnover intention were quantitated by self-completed questionnaire and measured by Likert 5–7 scale. Person correlation analysis, One-way ANOVA, and Structural Equation Modeling (SEM) were used for statistical analysis and mediating effect evaluation. Results Five hundred and sixty-four (45.3%) village public health providers had high turnover intension. Professional identity had a direct positive effect on job satisfaction (β = 0.146, p < 0.001), job satisfaction had a direct negative effect on burnout (β = 0.263, p < 0.001), and turnover intension (β = −0.453, p < 0.001), while burnout had a direct positive effect on turnover intension (β = 0.242, p < 0.001). Between professional identity and turnover intention, job satisfaction 95%CI: (−0.289)–(−0.11) had significant mediating effects. Job satisfaction 95%CI: (−0.216)–(−0.077) also had significant mediating effects between professional identity and burnout, and burnout had significant mediating effects between job satisfaction and turnover intension, 95%CI: (−0.116)–(−0.052). These results strongly confirm that professional identity, job satisfaction, and burnout are early and powerful predicators of turnover intention. Conclusion According to the results, medical administration and management departments should pay attention to improve the professional attraction of public health services by improving the public's understanding of the profession, reducing work intensity, timely granting of subsidy funds, improving old-age security, ensuring the income level, increasing the new force and so on, so as to reduce turnover intension and ensure the health equity of village residents.